Advanced gas leakage, fire and power supply failure monitoring system - Amirul Asraf Roslan; Rahimi Baharom (Institute of Advanced Engineering and Science, 2020)
Safety system such as smoke detector and fire alarm are considered to be a counter measure for fire accident. This safety system is important as it acts as a security measure against fire accident which could lead to death and destruction of properties. This paper propose an advanced gas leakage, fire and power supply failure monitoring system with Arduino UNO and GSM Module as its embedded system. Among the features of this system are their ability to detect the presence of smoke, gases and power failure at homes and factories, then the system will send a text message using Short Message Service (SMS) to the registered mobile number via GSM Module informing the user the situation and location of the incident. As a result, the user or person in charge can respond to the emergency situation accordingly and alert the fire departments or relevant authorities in time. This system could help the user to transform the way they protect their property and critical infrastructure. Successful safety and security transformation requires a combination of end user structural and operational changes as well as technology evolution enablement. This is in line with the Fourth Industrial Revolution (known as IR4.0), that propose substantial increase in the deployment of sensors for collecting, processing, and communicating measurement data in real time in order to diverse working environments, thus, resulting in advancement and convergence of technologies.